Strategi Peningkatan Produktivitas Petani Padi Sawah Terhadap Peranan Kelompok Tani di Desa Melati II - Andika Syaputra; Yusniar Lubis; Siti Sabrina Salqaura; Bambang Hermanto (Jurnal Ilmiah Pertanian ( JIPERTA), 2023)
This research is for indentified and evaluate element internal and ekstenal escalation produktivitas of farmer is fieldÂ  with the group of farmer in melati village ll. in this research, data analysis technique is using swot analysis withquantitative approach. the results of study shows that internally influence factors are legal entities, has aducation activity to farmers, group of farmer, has activity to farmer in order that can switch knowledge with other farmers from others village, keepingbook transfers regarding savings and loans, with the release of group farmer members there will be a reduction in the area of land for lowland rice production and the organizational structure is not working properly is a factor influencing the increase in productivity of lowland rice farmers on the role of farmer groups. Externally, the factor of influencing farmer are able to be used by tractor facilites and harvesting equipment, subsidized input facilities available to farmer groups, there are savings and loans for members of farmer groups, farmers consider organizational farmer groups to be unimportant, prices set for agricultural assistance tools are the same as tools conventional, and subsidized input facilities are not in accordance with the needs of farmers. Under these conditions, in general, the strategy for increasing the productivity of lowland rice farmers for the role of farmer groups in Melati II Village is that farmer groups have enormous strengths and opportunities to increase the productivity of lowland rice farmers for the role of farmer groups.